A New Analysis Method for Chemotaxis-Induced Instability in Multispecies Host-Parasitoid Systems. (28th February 2017) - Cao, Huaihuo
Abstract : We propose a new method applying matrix theory to analyse the instability conditions of unique homogeneous coexistent state of multispecies host-parasitoid systems. We consider the eigenvalues of linearized operator of systems, and by dimensionality reduction, this infinite dimensional eigenproblem will be reduced to a parametrized finite dimensional eigenproblem, thereby applying combinatorial matrix theory to analyse the linear instability of such constant steady-state.